A Review of Sustainable Tourism Curriculum on Higher Education - Chandra Budhi Septyandi; Mega Fitriani Adiwarna Prawira (Journal of Tourism Sustainability, 2022)
Global researchers have widely carried out publications on the tourism curriculum. The issue of sustainable tourism has been agreed upon as a platform for the development of world tourism. This study was conducted by studying reputable scientific articles on the tourism curriculum by connecting the two perspectives. Using the Systematic Literature Review (SLR) approach in the 2017-2022 scientific article, it was found that there are various pedagogical approaches to delivering sustainable tourism materials in universities. Student-based learning techniques were the determining factors for learning success, supported by the strategic partnership of higher education institutions with the tourism industry. Sustainable tourism learning in higher education was a long-term investment in tourism's human resources to realize tourism that can balance business, ecological and social benefits in the present and future.